Application of dust control method based on water medium humidification in tunnel drilling and blasting construction environment. (15th April 2023) - Sun, Hao; Liu, Yuhang; Jiang, Tengfei; Liu, Tong; Liu, Dedi
Abstract: The dust produced by tunnel drilling and blasting method is one of the most serious dust hazards, in which the original dust concentration produced during the blasting period far exceeds the requirements of China occupational health standards, which seriously affects the occupational health and safety of workers. Therefore, people pay more and more attention to how to effectively reduce the dust concentration. In this paper, the method of literature research is used to systematically summarize the dust-reducing technology of tunnel construction by drilling and blasting method. Firstly, the classification of dust during tunnel blasting period, physical and chemical characteristics of dust and its movement and diffusion are briefly introduced. Then, the dust wetting control technology during tunnel blasting period is sorted out, and the principle, advantages and disadvantages and application effect of various dust wetting control technology based on water medium are introduced. In view of the application limitation of single dust control technology, a series of improvement measures such as optimizing equipment parameters, combined dust control technology and application of special materials are put forward. Finally, the application of new technology of tunnel dust control is prospected. Highlights: The dust reduction technology of tunnel construction by drilling and blasting method is introduced. The physical and chemical characteristics and diffusion law of dust are summarized. The principle, advantages and disadvantages of dust humidification control technology are introduced In view of the limitations of dust control technology, improvement measures are proposed.